Defect Analysis of Packaging Bottle Products Using Six Sigma and Kaizen Methods at PT. XYZ - Muttaqin, Nashrotul Ummah Al; Aryanny, Enny (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
PT XYZ is a company engaged in manufacturing plastic packaging. The company produces various forms of packaging, one of which is cosmetic bottle packaging. Meanwhile, based on the problems of the production process, various types of product defects such as black spots, leaks, and oil dirt are often found. The company produces the most defective products in 30ml cosmetic bottle products, with a percentage of 3% to 4% of the total production. Based on the above problems, this study aims to determine the level of defects and the sigma value of product quality. In addition, provide suggestions for improvement to reduce the level of product defects at PT XYZ. The methods used are Six sigma and Kaizen. The Six Sigma stages include define, measure, analyze, and improve. The improve stage is assisted by the Kaizen Five M Checklist and Kaizen Five Step Plan. The improve stage is assisted by the Kaizen Five M Checklist and Kaizen Five Step Plan. Based on the results of research with the six sigma method, the percentage of black spot defects is 74%, leaking is 14.1%, and dirty oil is 11.9%. the proposed improvements given are providing 5S training and SOP refreshment, sorting reject products before grinding, cleaning the machine and production area at the end of each shift, replacing blowpin threads and bolts, and others.